Laparoscopic spleen-preserving distal versus central pancreatectomy for tumors in the pancreatic neck and proximal body. Issue 34 (August 2019) - Zhang, Hao; Xu, Qiaoyu; Tan, Chunlu; Wang, Xing; Peng, Bing; Liu, Xubao; Li, Kezhou
Abstract : Abstract: For benign and borderline tumors in the pancreatic neck and proximal body, laparoscopic spleen-preserving distal pancreatectomy (LSPDP) and laparoscopic central pancreatectomy (LCP) are alternative surgical procedures. Choosing between LSPDP and LCP is difficult. This retrospective cohort study was looking forward to provide evidence for clinical decision. A total of 59 patients undergoing LSPDP (Kimura procedure) and LCP between June 2013 and March 2017 were selected. The clinical outcomes of patients were compared by χ 2 test or Fisher exact test and Student t test. This study included 36 patients in LSPDP group, and 23 patients in LCP group. The overall complications incidence in LCP group was significantly higher than LSPDP group (35 vs 6%, P  = .004), and the postoperative pancreatic fistula (POPF) (grade B and C) rate and abdominal infection rate in LCP group were still significantly higher than LSPDP group (POPF 22 vs 3%, P  = .019; abdominal infection 35 vs 3%, P  = .001, respectively). The length of resected pancreas was significantly longer in LSPDP group (9.8 ± 2.0 vs 5.3 ± 1.1 cm, P  = .007). The median follow-up was 39 months (range 12–57 months). No patient was confronted by tumor recurrence. The proportion of postoperative pancreatin and insulin treatment in LCP group were similar to LSPDP group (9 vs 17%, P  = .383; 0 vs 3%, P  = 1.000, respectively). For patients with poor general condition, the safety of LCP needs to be taken seriously; in some ways, LSPDP may be more secure, physiological, and easier operation for tumor located in pancreatic neck and proximal body.